2020
DOI: 10.1007/s10212-020-00495-0
|View full text |Cite
|
Sign up to set email alerts
|

Nudging in education: from theory towards guidelines for successful implementation

Abstract: Nudging is one of the strategies from behavioral economics that aims to influence behavior by changing the environment. We propose that it could also be a valuable means to influence behavior in educational contexts. However, implementation of nudging in education is yet sparse. We describe the relevant issues to consider when applying nudging in education, arguing that a focus on the long-term effects and underlying processes of a nudge is necessary for successful implementation. Then, we aim to facilitate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 67 publications
0
50
0
1
Order By: Relevance
“…It is possible that the gains we detected are because feedback on this criterion was typically given early in the concept map creation process when students were more likely to subsequently make improvements to their concept maps. For future research, interesting avenues concern the differential effects of scaffolding, feedback, and the use of nudging techniques [42] for students with different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the gains we detected are because feedback on this criterion was typically given early in the concept map creation process when students were more likely to subsequently make improvements to their concept maps. For future research, interesting avenues concern the differential effects of scaffolding, feedback, and the use of nudging techniques [42] for students with different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…In education, recent work (Weijers et al, 2020) has stated that the application of nudging has been sparse, constituting a new research field. Nevertheless, the literature suggested that nudges impact engagement, task completion, and the study of learning resources (Kraft & Rogers, 2015;Martinez, 2014;van Oldenbeek et al, 2019;York et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Educational research demonstrates that particularly transparent type 2 nudges, i.e. nudges that also trigger reflective thinking and aim at changing deliberate choices, could be adjuvant with regard to EGB (Weijers et al, 2020). Schonger and Sele furthermore demonstrate that regarding infectious diseases, the way exponential growth is communicated, i.e.…”
Section: Ex Pon Enti a L Grow T H Bi As A N D Educationa L Nudgesmentioning
confidence: 99%